Arthrocentesis in companion animal medicine - PRASSINOS (N.N. ΠΡΑΣΙΝΟΣ), N. N.; SIDERI (K.I. ΣΙΔΕΡΗ), K. I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Arthrocentesis, especially for synovial fluid collection and analysis, is an integral part of any diagnostic joint evaluation in companion animal medicine. Although it is a simple, quick and inexpensive technique, which also requires little in the way of expertise or special equipment, it is a much under-employed procedure in veterinary diagnostics and/or therapeutics. Knowledge of joint anatomy, aseptic conditions and strict adherence to principles of the technique are essential for an uncomplicated arthrocentesis.